PENGARUH IMPLEMENTASI KEBIJAKAN STANDAR PELAYANAN MINIMUM TERHADAP KUALITAS PELAYANAN PENDIDIKAN PADA FAKULTAS ILMU SOSIAL DAN POLITIK UNIVERSITAS TADULAKO - Akhir, Abdi (Katalogis, 2017)
The purposes of this study were to determine the implementation influence of minimum service standards policy on educational services quality and also to identify the implementation influence of minimum service standards implemented into the internal policy on educational services quality at the Social and Political Sciences Faculty of Tadulako University. The theories used as footholds were the Policy Implementation Theory of Charles O. Jones (X Variables) comprising the dimensions of Organization, Interpretation, and Application and the Service Quality Theory of Rosenbloom (Y Variables) comprising the dimensions of Efficiency, Competence, and Fairness. The research method used was quantitative study. The sampling technique used was probability sampling, especially random sampling. Data were collected by means of questionnaire distributed to 88 respondents who were the implementors of the policy comprising the Faculty leadership elements, units leadership elements, and educators and educational personnels. Data were analyzed using multiple linear regression technique. The results showed that the implementation of minimum service standards policy referred to the theory of Charles O. Jones (1994) comprising the factors of organization, interpretation, and application partially had significant and positive influence on educational services quality at Social and Political Sciences Faculty of Tadulako University where the organization factor partially had sufficiently strong influence, the interpretation factor partially had sufficiently strong influence, and the application factor partially had strong influence on educational services quality at Social and Political Sciences Faculty of Tadulako University. While the simultaneous testing showed that the implementation of minimum service standards policy simultaneously had significant and positive influence on educational services quality at Social and Political Sciences Faculty of Tadulako University with strong level of influence closeness amounting to 26% while the rest 74% was owned by the other factors (epsilon) which is not detected.